Effectiveness of small-group sessions in enhancing students generic skills at the Shifa College of Nursing, Islamabad, Pakistan - Daredia, Afshan Saleem (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2013.